1997
DOI: 10.1111/j.1751-0813.1997.tb15366.x
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study of ovarian activity in fillies treated with a GnRH vaccine

Abstract: Both dose rates suppressed ovarian function and prevented oestrous behaviour. These effects were reversible and the subsequent fertility of the vaccinated fillies was normal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 23 publications
2
24
0
Order By: Relevance
“…1). Tshewang et al (1997) reported suppressed ovarian activity (follicles ≤ 1 cm) from approximately 3–4 weeks after first immunization in all mares. The present study (Table 1) showed that the interval from the first immunization until ovarian suppression (follicles ≤ 1 cm) was observed varied between the mares and that, within the same mare, the suppression did not start at the same time in both ovaries.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…1). Tshewang et al (1997) reported suppressed ovarian activity (follicles ≤ 1 cm) from approximately 3–4 weeks after first immunization in all mares. The present study (Table 1) showed that the interval from the first immunization until ovarian suppression (follicles ≤ 1 cm) was observed varied between the mares and that, within the same mare, the suppression did not start at the same time in both ovaries.…”
Section: Discussionmentioning
confidence: 96%
“…It has been shown that immunization against GnRH changed the oestrous behaviour of the animals. GnRH immunization caused a cessation of oestrous cycles in rats (Fraser and Baker, 1978), gilts (Esbenshade and Britt, 1985), ewes (Jeffcoat and Keeling, 1984), mares (Garza et al, 1986; Tshewang et al, 1997) and heifers (Wettemann and Castree, 1994; Prendiville et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies investigating the effect of GnRH vaccination have been carried out on mares, some documenting effective suppression of ovarian function and oestrous behaviour along with a subsequent reversal of these effects (Tshewang et al 1997), while others documented greater individual variation and a less reliable result (Dalin et al 2002).…”
Section: Immunization Against Gnrhmentioning
confidence: 99%
“…It comprises a peptide-protein conjugate and the Iscom-related immunostimulating complex adjuvant. This formulation is an advance over other commercial formulations trialed in mares and stallions that were reactogenic (50,178).…”
Section: Vaccines Against Reproductive Hormonesmentioning
confidence: 98%